Konsep Disgorgement Fund Antara Indonesia, India dan Amerika Serikat Melalui Studi Perbandingan Hukum - Tifani Rizki Dianisa; Adi Sulistiyono (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research aims to analyze the concept of Disgorgement Fund in Indonesia, India, and the United States through a comparative legal study approach. The Disgorgement Fund is a legal mechanism aimed at returning illegally obtained profits to the aggrieved parties and serves as a form of recovery for investors. The methodology employed includes analysis of legislation, court practices, and regulatory policies in the three countries. The findings indicate that while all three countries share the same goals in the implementation of the Disgorgement Fund, there are significant differences in the implementation and legal approaches taken. In the United States, the Disgorgement Fund is detailed by the Securities and Exchange Commission (SEC), while in Indonesia and India, it is still in the developmental stage and often influenced by local social and economic contexts. This research provides recommendations for enhancing the legal framework and implementation of the Disgorgement Fund in Indonesia and India, as well as offering a broader perspective on understanding the importance of investor protection in the context of the global capital market.